New anystid mite species (Trombidiformes, Prostigmata, Anystidae) from Ukraine - Pogrebnyak, S.G. (Збірник праць Зоологічного музею, 2010)
Tarsolarkus praeceps Pogrebnyak sp. n. is described from the semiforest zone of Ukraine. Mites were collected from soil surfaice and cereals grasses of steppefied slope. Tarsolarkus praeceps Pogrebnyak sp. n. описан с лесостепной зоны Украины. Клещи были отловлены на поверхности почвы и на злаковых травах остепненного склона. Tarsolarkus praeceps Pogrebnyak sp. n. описано з лісостепової зони України. Кліщі були здобуті на поверхні грунту та на злакових травах остепненого схилу.